Identification and characterization of IncL: a Chlamydia trachomatis protein associating with host cell lipid droplets and 14-3-3 proteins - Bugalhão, Joana Margarida Nunes (2022)
Chlamydia trachomatis causes genital and ocular infections in humans. This obligate intracellular bacterial pathogen multiplies within a characteristic vacuole, known as inclusion, and utilizes a type III secretion system to deliver chlamydial proteins, such as inclusion membrane proteins (Incs), into host cells. This work aimed to increase the knowledge on C. trachomatis Incs. A screen using Saccharomyces cerevisiae led to the identification of two Incs causing vacuolar protein sorting defects and seven Incs showing tropism for eukaryotic organelles. In particular, the transient production in yeast and mammalian cells of different fragments of CT006 (renamed IncL) revealed its tropism for the endoplasmic reticulum and lipid droplets (LDs), an organelle that regulates storage and hydrolysis of neutral lipids. We identified a LD-targeting region within the first 88 amino acid residues of IncL and positively charged residues important for this targeting. Comparing with the parental C. trachomatis strain, cells infected by a strain overproducing IncL showed a slight increase in the area occupied by LDs within the inclusion region. However, we could not correlate this effect with the LD-targeting regions within IncL. In addition, a previous proteomics screen suggested that IncL could bind mammalian 14-3-3 proteins, which regulate several signaling pathways in host cells. Here, co-immunoprecipitation assays validated the predicted interactions between IncL and 14-3-3β, η and γ isoforms and revealed an interaction with the 14-3-3σ isoform. The carboxy-terminal region of IncL was essential and sufficient for the IncL-14-3-3β interaction. We further showed that both the amino and carboxy-terminal regions of IncL, flanking the Inc-characteristic bilobed hydrophobic domain, are exposed to the host cell cytosol during C. trachomatis infection, and therefore available to interact with host cell targets. In conclusion, we characterized a chlamydial protein interacting with host cell LDs and 14-3-3 proteins via different protein regions, thus expanding the understanding of C. trachomatis-host cell interactions.